Asymmetry in men`s artistic gymnastics - Hedbavny, P. (International Scientific Congress Slovenian Gymnastics Federation, 2019)
A complex temporo-spatial structure of gymnastic exercise is not symmetrical in all elements. The aim of this study is to find out whether there are any side differences in one of upper and/or lower extremities when comparing stand to handstand performance and how these changes related to other factors such as amount of muscles and laterality. 13 gymnasts tried to maintain static balance for 10 seconds in standing position and in handstand, each measurement was performed 5 times. Measurements were perfomed using 2 Bertec force plates. A device InBody 720 was used to diagnose the amount of muscle tissue of upper and lower extremities. The results of dynamic measurements showed statistically significant difference between the loads of one (more loaded) and second (less loaded) lower extremity during the standing position (p = .000) as well as during handstand with regard to upper extremities (p = .003). The analysis of the amount of muscle tissue on extremities showed a statistical significant difference between the upper extremities (p = .002) and lower extremities (p = .000). Pearson correlation coefficient did not prove a relation between observed variables. To conclude, we recommend paying attention to symmetrical performance of the gymnastics elements which are symmetrical in their structure.